2015
DOI: 10.3126/hren.v12i2.14120
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body stone in oesophagus: a unique case

Abstract: Foreign body ingestion is a common occurrence in children and in specific high-risk  groups. It is usually diagnosed based on a history of ingestion given by the patient  or an observer. However, children and mentally retarded adults may be unable to  give an accurate history, and a high index of suspicion must be maintained in these  groups. We report a rare case of foreign body stone in an mentally retarded adult  which presented with drooling and impaired feeds, thence enabling for high index  for suspicion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…There are limited case reports of stone impaction in the esophagus in the literature. Sah et al 16 reported the case of a 35-yearold man with delayed cognitive development in Nepal who swallowed a stone and had it removed from the cervical esophagus through rigid upper endoscopy. Zameer et al 17 described a 25-day-old neonate who presented with a large stone in the upper esophagus that unfortunately was unable to be removed and resulted in esophagotomy.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited case reports of stone impaction in the esophagus in the literature. Sah et al 16 reported the case of a 35-yearold man with delayed cognitive development in Nepal who swallowed a stone and had it removed from the cervical esophagus through rigid upper endoscopy. Zameer et al 17 described a 25-day-old neonate who presented with a large stone in the upper esophagus that unfortunately was unable to be removed and resulted in esophagotomy.…”
Section: Discussionmentioning
confidence: 99%